Association between bone characteristics and cardiovascular risk factors among adults in selected urban areas in Selangor, Malaysia - Mohamad Ismuddin, Safarina (2021)
Cardiovascular disease (CVD) and osteoporosis (OP) are two significant public health-care issues globally with increased morbidity and mortality. The rising proportion of the ageing population globally indicates that urgent action is required to tackle the projected burden of CVD and OP. Increasing evidence now supports a direct association between these chronic conditions. Understanding this link in pathophysiology is important for the prevention and treatment of these disorders. Previous studies have revealed contradicting associations between CVD and OP. The escalating prevalence of OP and CVD globally with its increased morbidity and mortality notwithstanding the contradictory results on their association stresses the need for further research on this topic. No previous study has evaluated bone characteristics with Pattern B lipoprotein profile, which are individuals with atherogenic small dense low density lipoprotein cholesterol (LDL) particles. Hence this study aimed to determine the associations between bone characteristics and CVD risk factors, including Pattern B among adults in selected urban areas in Selangor, Malaysia. This was a cross sectional study involving 331 healthy subjects aged ≥ 45 years old from three selected residential areas in Puchong, Serdang, and Kajang, who were invited for a health screening at Puchong Specialist Centre. Recruitment was by convenience nonrandom sampling. Sociodemographic factors and clinical characteristics were recorded in the proforma after informed consent. Biochemical analyses on fasting samples were outsourced to Pantai Premier Laboratory. Data analysis was done using IBM SPSS Statistic version 25.0 for Windows. The prevalence of osteopenia and osteoporosis are 41.4% and 17.2%, respectively. Pattern B is detected in 48.9% with 39.9% having metabolic syndrome (MetS). Waist circumference (WC) and high-density lipoprotein cholesterol (HDL) are associated with abnormal bone mineral density (BMD) status and increased WC, hyperglycaemia, deranged lipid profile and MetS are associated with a higher BMD. The association between WC, fasting blood sugar (FBS), triglyceride (TG) with BMD, respectively is not driven by total fat since the associations remained highly significant after adjustment for total fat. However, it is gender-specific. For HDL and MetS, however, this association with BMD is driven by total fat in females as it becomes attenuated after adjusting for it. A higher BMD is reported among MetS subjects but the effects of MetS on BMD varied by gender and skeletal site. Apart from the bone resorption marker, c-terminal telopeptide of type 1 collagen (CTX), there was no significant association between Pattern B and bone parameters. However, after adjusting for age, gender, race and total fat, there was no significant difference for CTX between Pattern A (individuals with non-atherogenic large buoyant LDL) and Pattern B. The only significant bone parameter associated with MetS is Mg, which is a protective factor. This study’s results suggest that there are skeletal site and gender specific differences in the association between CVD risk factors with abnormal BMD status and BMD per se. The relative contribution of these risk factors would vary with skeletal sites considering that the rate of bone loss at different skeletal sites are diverse due to the variations in the composition of each bone and the heterogeneity in bone microstructure. A higher BMD was demonstrated among MetS subjects but the effects of MetS on BMD varied by gender and skeletal site. The only significant bone parameter associated with MetS in this study is Mg, which is a protective factor. MetS is a combination of CVD risk factors that include obesity, a factor associated with increased BMD, and inflammation, a factor that lowers BMD. In this study, the findings suggest that adiposity may have a protective effect on BMD.